Ontology of Time as a Deconstruction of Space. An Essay on the Philosophy of Byzantine Music - Solunchev, Risto (Conatus - Journal of Philosophy, 2019)
In this paper the author examines the ontology of Byzantine music in its self, its aesthetical ground, the philosophical and cultural principles of creation, its episteme, the epistemological field that produced its forms from the 12th till the 14th century, and why that musical ontology hasn’t change through the centuries. The paper discusses in partucular Ernst Bloch’s view that the only evolutionary expression of the Absolute spirit as far as music is concerned, is Western classical music. The author claims that the Western and the Byzantine music stand for two totally distinct and diverse ontologies of the musical being, something that Bloch seems to overlook; this, according to the author, is mostly due to the different systems of representation that have been used, and especially the representational ideas of the time-space relation. The author supports the view that while Western music is spatially-modeled, Byzantine music is time-modeled.